The effect of thai glutinous rice starch on the synthesis of lead zirconate (PbZrO3) nanofibers via the electrospinning method - Nawanil, Chanisa; Vittayakorn, Wanwilai; Muanghua, Rangson; Niemcharoen, Surasak; Prachayawarakorn, Jutarat; Vittayakorn, Naratip (My University, 2013)
This study synthesized blended lead zirconate (PbZrO3;PZ)/ poly(ethylene oxide)(PEO)/Glutinous rice starch (GRS) nanofibers by the electrospinning method. A number of parameters such as the ratio between PEO and GRS and calcination temperature have been studied. The as-spun PZ/PEO/GRS composite and PZ fibers were characterized by TG-DTA, X-ray diffraction, FT-IR and SEM, respectively. SEM results showed that smooth and continuous fibers were obtained at the volume ratio of 10:2:1, PZ/PEO/GRS. After calcination of the as-spun PZ/PEO/GRS composite nanofibers at 650 °C for 4 h, PZ nanofibers with perovskite structure were obtained successfully. The fibers had a uniform and smooth surface without grain boundaries. However, when the calcination temperature increased to 750 °C and 850 °C, the fiber represented a necklace-like structure with grain boundaries arranged by grain to grain unit cell clusters. Copyright © 2013 American Scientific Publishers.
Keywords: Electrospinning; GRS; PEO; PZ; Sol-gel